1994
DOI: 10.1128/aac.38.5.1008
|View full text |Cite
|
Sign up to set email alerts
|

Preferential incorporation of nucleoside analogs after template switching during human immunodeficiency virus reverse transcription

Abstract: We assessed the effects of 3'-azido-3'-deoxythymidine (AZT), 2',3'-dideoxyinosine (ddl), and the (-) enantiomer of 2',3'-dideoxy-3'-thiacytidine (3TC) on reverse transcription in CD4-positive cells by isolating truncated human immunodeficiency virus (HIV) DNA fragments. Jurkat cells were treated with AZT (2 ,LM), ddl (200 ,uM), or 3TC (50 ,uM) The reverse transcriptase (RT) of the human immunodeficiency virus (HIV) is essential for the formation of the viral double-stranded DNA genome from its RNA templates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
56
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 36 publications
9
56
1
Order By: Relevance
“…AZT chain-terminated DNA is incapable of promoting further elongation, because of the absence of a 3' hydroxyl group (Zack et al, 1992). We have also shown, by quantitative PCR amplification, that AZT can chain-terminate elongating viral DNA in activated peripheral blood lymphocytes, quiescent brain macrophages (Geleziunas et al, 1993) and Jurkat cells (Arts & Wainberg 1994). We found that chain termination by AZT in viral particles occurred only after the first template switch, which is consistent with the mode of action of nucleoside analogues in HIV-infected cells (Arts & Wainberg, 1994).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…AZT chain-terminated DNA is incapable of promoting further elongation, because of the absence of a 3' hydroxyl group (Zack et al, 1992). We have also shown, by quantitative PCR amplification, that AZT can chain-terminate elongating viral DNA in activated peripheral blood lymphocytes, quiescent brain macrophages (Geleziunas et al, 1993) and Jurkat cells (Arts & Wainberg 1994). We found that chain termination by AZT in viral particles occurred only after the first template switch, which is consistent with the mode of action of nucleoside analogues in HIV-infected cells (Arts & Wainberg, 1994).…”
Section: Discussionsupporting
confidence: 68%
“…We have also shown, by quantitative PCR amplification, that AZT can chain-terminate elongating viral DNA in activated peripheral blood lymphocytes, quiescent brain macrophages (Geleziunas et al, 1993) and Jurkat cells (Arts & Wainberg 1994). We found that chain termination by AZT in viral particles occurred only after the first template switch, which is consistent with the mode of action of nucleoside analogues in HIV-infected cells (Arts & Wainberg, 1994). However, virus generated in the presence of AZT was as infectious as wild-type for H9 cells, suggesting that HIV genome-derived DNA is not involved in infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One problem that may be frequently encountered during prolonged administration of nucleoside analogs is the selection of HBV resistant strains with mutation in the viral polymerase as already described with antiviral therapy of HIV infection. 1,13 Sequence alignment and comparison with the crystal structure of the HIV reverse transcriptase have shown that most of the mutations associated with resistance to famciclovir or lamivudine reside in domains B and C of the HBV polymerase. [14][15][16] Resistant viruses, with mutations in the catalytic site (domain C) of the viral polymerase (M539V and M539I), similar to that observed in HIV resistant strains to Abbreviations: HBV, hepatitis B virus; PCR, polymerase chain reaction; ALT, alanine aminotranferase; HBsAg, hepatitis B surface antigen; HBeAg, hepatitis B e antigen; tid, thrice daily.…”
mentioning
confidence: 99%